2021
DOI: 10.3390/su13179740
|View full text |Cite
|
Sign up to set email alerts
|

Application of Granular and Non-Granular Organic Fertilizers in Terms of Energy, Environmental and Economic Efficiency

Abstract: Granular organic fertilizers have been increasingly used in agriculture due to the longer delivery of nutrients to plants and the milder impact on the environment. The aim of this study was to determine the energy, environmental and economic efficiency of granular and non-granular organic fertilizers. Four technological scenarios of organic fertilizer use were used for comparative assessment: (1) manure fertilization (16.0 t ha−1), (2) manure fertilization (30.0 t ha−1), (3) manure pellet fertilization (2.0 t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…These coefficients take into account changes in the overall efficiency of working processes with the change in the degree of power utilization of energy sources, e.g., engines. In the case of manual work, the energy utilization coefficient (β11), which is equivalent to the term "energy equivalent of working time" [37] used in the literature, is 1.96 MJ/man-h. As a result of the use of energy utilization coefficients in the calculation procedure, the usable energy (E11u, E12u, and E13u) is expressed in MJ units. Due to the expression in the same units, the usable energy components can be used to calculate the technological index level (T L ).…”
Section: The Procedures For Calculating the Technological Index Levelmentioning
confidence: 99%
“…These coefficients take into account changes in the overall efficiency of working processes with the change in the degree of power utilization of energy sources, e.g., engines. In the case of manual work, the energy utilization coefficient (β11), which is equivalent to the term "energy equivalent of working time" [37] used in the literature, is 1.96 MJ/man-h. As a result of the use of energy utilization coefficients in the calculation procedure, the usable energy (E11u, E12u, and E13u) is expressed in MJ units. Due to the expression in the same units, the usable energy components can be used to calculate the technological index level (T L ).…”
Section: The Procedures For Calculating the Technological Index Levelmentioning
confidence: 99%
“…In the case of garden waste compost, Lata and Marschner (2013) reported that adding the finest fraction (<3 mm) increased microbial biomass and P availability in soils more than the equivalent coarser fraction (>5 mm). Also, pellet diameters should be between 4 and 6 mm to ensure an even spread when using mineral or organic fertilizer spreaders (Šarauskis et al., 2021). The use of granulated organic fertilizers is becoming more popular in sustainable agriculture, especially since less fertilizer is needed compared to traditional compost amendment (Šarauskis et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Also, pellet diameters should be between 4 and 6 mm to ensure an even spread when using mineral or organic fertilizer spreaders (Šarauskis et al., 2021). The use of granulated organic fertilizers is becoming more popular in sustainable agriculture, especially since less fertilizer is needed compared to traditional compost amendment (Šarauskis et al., 2021). The application of granulated organic fertilizers also has beneficial long‐term effects on soil fertility, including increasing the availability of P and K and the content of TOC and humus (Mieldažys et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A szemcsés szerves trágyák átlagos ammónia (NH3) kibocsátása hatszor alacsonyabb, mint a nem szemcsés szerves trágyáké. A különböző szerves trágyák lézerspektroszkópia elve szerinti elemzése kimutatta, hogy a szemcsés szerves trágyák 97,8%-kal csökkentik az NH3 kibocsátás negatív környezeti hatását a nem szemcsés trágyához képest [11]. Az istállótrágya 17,5%-os szárazanyag tartalmához viszonyítva a korszerű szervestrágya pellet általában 90%-os szárazanyag tartalommal bír.…”
Section: Irodalomunclassified